1998
DOI: 10.1002/pro.5560071119
|View full text |Cite
|
Sign up to set email alerts
|

Prediction by a neural network of outer membrane β‐strand protein topology

Abstract: An artificial neural network (NN) was trained to predict the topology of bacterial outer membrane (OM) beta-strand proteins. Specifically, the NN predicts the z-coordinate of Calpha atoms in a coordinate frame with the outer membrane in the xy-plane, such that low z-values indicate periplasmic turns, medium z-values indicate transmembrane beta-strands, and high z-values indicate extracellular loops. To obtain a training set, seven OM proteins (porins) with structures known to high resolution were aligned with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 58 publications
0
50
0
Order By: Relevance
“…Kleivdal et al (1999) recently identified positively charged amino acids in the FomA protein that were found to be important to pore function, which supported the topology model, where these amino acids are predicted to be located in transmembrane segments 5 and 6 and contribute to a hydrophilic pore lumen. In addition, when the FomA protein sequences were subjected to the recently published neural network topology prediction method (Diederichs et al, 1998), a virtually identical topology model was predicted (Fig. 1b), in spite of the fact that the FomA proteins have no sequence similarity to the proteins used to train the neural network.…”
Section: Discussionmentioning
confidence: 84%
“…Kleivdal et al (1999) recently identified positively charged amino acids in the FomA protein that were found to be important to pore function, which supported the topology model, where these amino acids are predicted to be located in transmembrane segments 5 and 6 and contribute to a hydrophilic pore lumen. In addition, when the FomA protein sequences were subjected to the recently published neural network topology prediction method (Diederichs et al, 1998), a virtually identical topology model was predicted (Fig. 1b), in spite of the fact that the FomA proteins have no sequence similarity to the proteins used to train the neural network.…”
Section: Discussionmentioning
confidence: 84%
“…Neural networks have been largely employed in biochemistry and correlated research fields such as protein, DNA/RNA and molecular biology sciences [121][122][123][124][125][126][127].…”
Section: Biochemistrymentioning
confidence: 99%
“…In fact, even for the predictive methods that are capable of identifying OMPs, precision remains poor [4,8,14,19,25,28]. Furthermore, the datasets used to train and evaluate these existing methods are often small and not manually curated.…”
Section: Related Work 21 Work On Related Problemsmentioning
confidence: 99%
“…Scientists have previously used neural network-based methods [4,8], hydrophobicity analysis [19], and combinations of methods, including homology analysis and amino acid abundance [25,28], to varying degrees of success. The most recent approach, reported by Martelli et al [14] is, to date, the most successful attempt at OMP classification.…”
Section: Related Work 21 Work On Related Problemsmentioning
confidence: 99%